Interesting coincidence of liver abscess secondary to foreign body and gastric inflammatory fibroid polyp - Catherine Behzad; Mohammad Reza Hasanjani Roushan; Abolhasan Alijanpour; Hossein Ghorbani; Hossein Shahabandaz (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Behzad C, Hasanjani Roushan MR, Alijanpour A, Ghorbani H, Shahabandaz H. Interesting coincidence of liver abscess secondary to foreign body and gastric inflammatory fibroid polyp. Turk J Gastroenterol 2020; 31(9): 673-5.